Pengaruh Kompensasi, Jenjang karir, dan Kepuasan Kerja terhadap Turnover pada Karyawan PT Hartono Surabaya, Cab Bukit Darmo - Wisnu Jati Jaya Kusuma; Tan Evan Tandiyono (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
In recent years, companies engaged in technology have experienced significant growth in various countries, including in indonesia, PT Hartono is a company that sells technological goods to faciliate/fulfill the needs of society in this modern era, with various technologies that have been specifically designed so that consumers feel interested in what consumers need or what consumer want, the data analysis technique that will be used for this research is quantitative research using multiple linear regression methods. And the data collection design was a questionnaire, the population in this study were all warehous employes at PT Hartono, which totaled 68 people, because each branch had a different procedure so that researchers took samples of branch that were in the Bukit Darmo Surabaya Branch. Data analysis used multiple linear regression analysis, classical assumption test, model feasibility test, hypothesis testing (T-test). How consumer see and perceive the company.